Deteksi Titik Panas dan Pola Spasio-Temporal Kejadian Penyakit Demam Berdarah Dengue Di DKI Jakarta - Rere Kautsar; Bagus Sartono; Cici Suhaeni; Bimandra Adiputra Djaafara (Xplore: Journal of Statistics, 2019)
Dengue virus is one of the causes of infectious diseases in human with mosquitoes as vector of transmission. In Jakarta, dengue infection is still one of the most important health problems, particularly its severe clinical manifestation which is known as dengue hemorrhagic fever (DHF). Spatio-temporal approach was used in this research to analyze the spatial pattern of DHF spread in Jakarta. The data used for analysis are consisted of total number of people suffering from DHF in Jakarta at the sub-district per week, monthly total precipitation, and the total population each sub-district in DKI Jakarta per year since 2008 until 2016. Incidence rate of dengue fever in Jakarta tend to be higher in March to April period compared to the other months. The spread of DHF burden tend to be clustered during the period of 2008 until 2011 whereas in the next five years, clustered pattern was not observed. The hotspots of DHF cases were more likely to occur in the north, east, and south part of DKI Jakarta.